Kandungan Fitokimia dan Aktivitas Antioksida dari Daun Tumbuhan Senduduk (Melastoma malabathricum L.) dengan Metode GC-MS (Gas Chromatography-Mass Spectrometry) - Afrizal, Afrizal; Wirawan, I Gede Putu; Darmawati, Ida Ayu Putri (Agrotrop : Journal on Agriculture Science; Vol 13 No 3 (2023), 2023)
Phytochemical Content and Antioxidant Activity of the Leaves of the Senduduk Plant ( Melastoma malabathricum L.) using the GC-MS ( Gas Chromatography - Mass Spectrometry ) Method. Senduduk ( Melastoma malabathricum L) is one of the plants that can be used as traditional medicine. This study aims to determine the types of active compounds, levels of active compounds, and levels of antioxidant compounds in the leaves of the senduduk plant. This research lasted for 3 months. The method used in this study is a descriptive method with laboratory analysis techniques. Active compound analysis testing with GCMS analysis, testing and phytochemical levels, as well as determining the activity and levels of antioxidants. The results showed that the active compounds in senduduk leaf extract were mostly dominated by phenolic compounds and saponin compounds. The phenolic compound group contains active compounds 1,2,3-Benzenetriol and Vitamin e dl-.alpha.-Tocopherol with a percentage of 26.252% and the saponin group contains active compounds by fatty acids, namely hexanacanoic acid and linoleic acid with an area proportion of 14.25. %. The levels of active compounds from the phytochemical screening of the active compound group with the strongest levels were Alkaloids, Phenolics, and Saponins. The active compound group with moderate levels was only terpenoid active compounds, while the active compounds with sufficient levels contained steroids, flavonoids, and tannins which were tested by the Liebermann, Buchard, and Meyer reagent examination methods. The antioxidant activity in the extract of the leaves of this senresiden is strong enough, namely 70,607 ppm.